Mengembangkan Potensi Kewirausahaan Karya Seni Lukis Papua Pada Kalangan Anak Muda GKI Siloam - Maria Maya Burdam; Ahmad Rezkiyadi Pratama; Imanuella Desanti Toisuta; Marice Yosefin Maniburi; Susana Magdalena Welly Muskita (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Papua is an island located in the eastern part of Indonesia. This island is famous for its various natural riches, agricultural products and unique culture. In the era of globalization, Papuan culture has experienced a drastic decline, with many young people abandoning their culture as native Papuans and following the times with modern culture. Without them realizing, there are many aspects and opportunities that can be developed to help the economy and can even introduce the world to the beauty of Papua through the art of painting. One of the characteristics of Papua is the beauty of the bird of paradise. This beauty can be used as an illustration of business potential by making art paintings of birds of paradise. Young people must play an important role in promoting the beauty of Papuan paintings through social media and showing the world that the potential of young people to produce works can be appreciated.